Outbreak of Mycobacterium avium subsp. avium infection in one flock of domestic pigeons - Kriz, Petr; Slana, Iva; Králík, Petr; Babak, Vladimir; Skoric, Misa; Fictum, Petr; Docekal, Jan; Pavlik, Ivo (Avian diseases, 2011)
An outbreak of Mycobacterium avium subsp. avium infection was diagnosed in one breed of domestic pigeons (Columba livia f. domestica) in the Czech Republic. Nodular granulomatous lesions were found in 42 (9.7%) pigeons of the 435 examined; histopathologic examination of livers with gross lesions of mycobacteriosis from 15 randomly selected pigeons revealed granulomatous inflammation typical for avian mycobacteriosis in all samples. Direct Ziehl-Neelsen (ZN) microscopy and conventional culture were performed for a total of 117 liver samples (42 pigeons with nodular lesions, 55 randomly selected pigeons without nodular lesions, and 20 randomly selected squabs). Acid-fast bacilli were observed in 19 (16.2%), and conventional culture yielded growth of M. a. avium in 40 (34.2%) liver samples. A triplex quantitative real-time PCR assay based on the IS901 detection system was performed successfully in 115 liver samples and revealed M. a. avium in 63 (54.8%) of them. Mycobacterium a. avium was also detected in two squabs. Eight domestic rabbits (Oryctolagus cuniculus f. domestica) living in the breeding facility were also examined. Pyogranulomatous lesions were only found in one adult male rabbit. At necropsy, both direct ZN microscopy and culture gave negative results for mycobacteria in all examined rabbit tissues. Mycobacterium a. avium was diagnosed in a liver sample of one juvenile rabbit using triplex qPCR, suggesting that M. a. avium infection can occur as early as juvenile animals.
Keywords: Liver; Animals; Rabbits; nemoci jater; ptačí tuberkulóza; Female; játra; polymerázová řetězová reakce; Polymerase Chain Reaction; ženské pohlaví; nemoci ptáků; Mycobacterium avium; Columbidae; Bird Diseases; Tuberculosis; Liver Diseases; Male; Czech Republic; Tuberculosis, Avian; tuberkulóza; Česká republika; králíci; zvířata; mužské pohlaví